Post a New Question

Math

posted by .

For Reiny:What step did I do wrong.(Help)

(x-4x^3)^2
=(x-4x^3)(x-4x^3)=(x)(x)+(x)(-4x^3)+(-4x^3)(x)+(-4x^3)(4x^3)

= x^2-4x^4-4x^4-16x^6
=x^2-8x^4-16x^6

  • Math -

    Your answer is correct. You did nothing wrong.

  • Math -

    -16x^2=>+16x^2

  • check this again - Math -

    should have looked a bit more carefully

    the last term should be + 16x^6

    (in your second line: should have been

    =(x-4x^3)(x-4x^3)=(x)(x)+(x)(-4x^3)+(-4x^3)(x)+(-4x^3)(-4x^3)

  • Math -

    Thanks Reiny, Thanks Anonymous I went over it and found the problem.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question